Developing Intercultural Mindedness through an Experiential Learning Activity-A Case Study from Singapore - Heidi Layne; Siao See Teng (MDPI AG, 2022)
Recent incidents of alleged racism worldwide amid the COVID-19 pandemic have challenged us to ponder on the meaning and importance of intercultural education. However, it can be difficult to understand the ways in which intercultural discourse can be beneficial for learning, as well as prepare young people to act against racism and inequalities to work towards a more sustainable future. This study presents analysis of learning materials from a case study conducted in one secondary school in Singapore. The objective of the activity is for students to engage in intercultural learning by participating in walking trails with different themes in a few neighborhoods, to learn more about the history of and life in multiracial Singapore. Researchers followed and observed the two-day event and collected data from the students. Specifically, written reflections from a trail named Many Races-One Nation were collected from the students, as well as their reflective posters at the end of the event. The content analysis of these artefacts concentrates on the meanings and ideologies underlying intercultural learning through an examination of the learning materials and the students' responses. Furthermore, this study introduces an intercultural mindedness framework that transcends the conflict avoidance approach for deeper learning.